2019
DOI: 10.1038/s41598-019-44130-5
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive laser treatment combined with intravitreal injection of anti-vascular endothelial growth factor for diabetic macular oedema

Abstract: The purpose of this study was to investigate the effect of the combination of minimally invasive laser treatment to the intravitreal injection of anti-vascular endothelial growth factor (VEGF) for diabetic macular oedema (DME). This study was retrospective longitudinal study of thirty-four eyes of 31 patients with DME. Either once or several times of intravitreal anti-VEGF injection was followed by the single minimally invasive laser within a month. The mean best corrected visual acuity (VA) and the central ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Nevertheless, they were analyzed because they documented the results of combined therapy. Two trials compared the outcome of combination treatment versus SDM alone [15,16], and two studies presented the effects of combination treatment in specific cases of ME [17,18]. A description of these four studies is provided in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, they were analyzed because they documented the results of combined therapy. Two trials compared the outcome of combination treatment versus SDM alone [15,16], and two studies presented the effects of combination treatment in specific cases of ME [17,18]. A description of these four studies is provided in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Although the results suggested the occurrence of significant morphological and functional improvements, the trial did not include a control group, so it was not possible to assess how the addition of SDM to intravitreal dexamethasone affected the final outcome. A study by Inagaki et al, which considered SDM and anti-VEGF therapy in DME is a case series, [18] observed a moderate BCVA improvement (by 0.11 logMAR), with a relatively low number of injections required to achieve this effect during one year of follow-up (mean: 3.6 ± 2.1 injections).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing clinical evidence for the effectiveness of these laser treatments. [14][15][16][17][18][19][35][36][37][38] Thus, a laser system that enables one to choose the treatment modality properly according to the purpose, selective RPE destruction, mild hyperthermia, or classical photocoagulation with desired strength is very useful. Moreover, it would be also highly valuable to have a method that can monitor and display the tissue response during treatment sensitively.…”
Section: Discussionmentioning
confidence: 99%
“…Inagaki et al showed recently, that combining anti-VEGF injections and minimally invasive laser treatment in DME results in good anatomical and functional improvement at 12 months [ 20 ]. While the visual gain in the study of Inagaki et al was slightly worse (5.9 ETDRS letters), than in previous prospective studies for anti-VEGF therapy alone (6.6–10.3 EDTRS letters in REVEAl, RESTORE and RESOLVE), the mean number of injections was as low as 3.6 12 months after treatment.…”
Section: Discussionmentioning
confidence: 99%